2015
DOI: 10.3390/ma8095300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrafine 2CaO·SiO2 Powder on Hydration Properties of Reactive Powder Concrete

Abstract: In this research, we assessed the influence of an ultrafine 2CaO·SiO2 powder on the hydration properties of a reactive powder concrete system. The ultrafine powder was manufactured through chemical combustion method. The morphology of ultrafine powder and the development of hydration products in the cement paste prepared with ultrafine powder were investigated by scanning electron microscopy (SEM), mineralogical composition were determined by X-ray diffraction, while the heat release characteristics up to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, the scope of these design codes is limited to traditional concrete types and the relatively new type of materials including RPC are not covered in it. However, in the last decade, extensive studies were reported for RPC and UHPC, especially at ambient temperature [18,19,20,21]. In spite of a promising material at ambient temperature, fire-induced spalling limits its application to buildings and the current design codes allows us to use only up to Class C90/105 for concrete structures [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the scope of these design codes is limited to traditional concrete types and the relatively new type of materials including RPC are not covered in it. However, in the last decade, extensive studies were reported for RPC and UHPC, especially at ambient temperature [18,19,20,21]. In spite of a promising material at ambient temperature, fire-induced spalling limits its application to buildings and the current design codes allows us to use only up to Class C90/105 for concrete structures [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results of reduced setting time were obtained in [28], where nano-TiO2 was added to the cement composites. The results presented by [29] showed that the setting time can also be delayed by adding 2CaO⋅SiO2 nanoparticles to the concrete. The literature and the obtained results confirm that the nanoparticles have an impact on the setting time of concrete or cementitious composites.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, complex structural and internal loading conditions require the piles to be made of superior performance material such as ultra-high performance concrete (Tulebekova et al, 2019). Reactive Powder Concrete (RPC) is a type of ultra-high performance concrete that is obtained by removing coarse aggregates from and addition of pozzolanic materials like silica fume (SF) to the concrete along with very low waterto-binder ratio (w/b) (Sun et al, 2015). RPC has a densified microstructure that is attributed to the removal of coarse aggregates and the pozzolanic reaction that lead to the formation of strong bonds in interfacial transition zone due to the increased formation of strong calcium silicate hydrate lattices (Beglarigale and Yazıcı, 2015).…”
Section: Introductionmentioning
confidence: 99%